REBASE—restriction enzymes and methylases - Roberts, Richard J. (Oxford University Press, 2001)
REBASE contains comprehensive information about restriction enzymes, DNA methylases and related proteins such as nicking enzymes, specificity subunits and control proteins. It contains published and unpublished references, recognition and cleavage sites, isoschizomers, commercial availability, methylation sensitivity, crystal data and sequence data. Homing endonucleases are also included. Most recently, extensive information about the methylation sensitivity of restriction enzymes has been added and a new feature contains complete analyses of the putative restriction systems in the sequenced bacterial and archaeal genomes. The data is distributed via email, ftp (ftp.neb.com) and the Web (http://rebase.neb.com).